Analisis Efektivitas dan Desain Pelaporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah Pada Kafil Cell - Anjasmara Anjasmara; Muhammad Yamin; Rina Novianty (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research analyzes the effectiveness and design of Kafil Cell's financial reporting based on the Financial Accounting Standards for Micro, Small and Medium Entities. Using qualitative descriptive methods with interviews and documentation, this research found that Kafil Cell's financial reporting was not fully in accordance with financial accounting standards for micro, small and medium entities, only focusing on profit and loss statements without balance sheets and notes to financial statements. Reporting ineffectiveness can be seen from untimeliness, lack of completeness of information, and manual recording. A more structured reporting design based on accounting standards will help increase financial transparency and accountability. This research provides recommendations for implementing a more structured recording system and adjusting the financial report format to comply with standards.